A systematic review on risk factors for khat chewing among adolescents in the African continent and Arabian Peninsula - Fiidow, Osman Abubakar; Minhat, Halimatus Sakdiah; Mohd Zulkefli, Nor Afiah; Ahmad, Norliza (PLoS ONE, 2022)
Introduction: Khat is a flowering plant with stimulant effect on the nervous system and produce psychological dependence. Despite its harmful effects, the ingestion of khat has been part of cultural norms and the legality of khat varies by region. Objective: This systematic review aimed at critically evaluating the available evidence on the risk factors of khat chewing among adolescents. Methods: A systematic review was conducted on published research studies from five databases Scopus, PubMed, Science-direct, Ovid and google scholar using keywords khat chewing OR qat chewing AND associated factors OR risk factors OR contributing factors AND adolescents OR teenagers. Articles included were either cross-sectional, cohort, case-control or qualitative studies which were published between the year 1990 till present. Excluded articles were the non-English written articles, descriptive studies and irrelevant topics being studied. Results: Out of 2617 records identified and screened, six were included for the analysis and interpretation of the data. All included studies were cross-sectional study design. All six studies reported having family members who chewed khat significantly predict khat chewing among adolescents, followed by five articles for friends or peers who also chewed khat and four articles for male gender. Smoking was also found to have the highest odds (OR = 18.2; 95% CI: 12.95–25.72) for khat chewing among adolescents. Conclusion: The review highlights the crucial role of family members, friends or peers and male gender to predict khat chewing among adolescents. Effectiveness of health promotion programs to educate and reduce khat chewing among adolescents will require active participation of family members and friends.